Comparing ultraviolet and chemical reduction techniques for enhancing photocatalytic activity of silver oxide/silver deposited nanocrystalline anatase titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K.; Warrier, K. G. K. (Journal of Physical Chemistry C, 2009)
Silver oxide/silver have been deposited, with varying silver concentration (0.01-10 mol %), on the surface of sol-gel derived nanocrystal line anatase titania using two different techniques, namely the ultraviolet reduction and chemical reduction (using stannous ions). The pure and silver oxide/silver-deposited nanocrystalline anatase titania have been characterized for their morphology, average nanocrystal lite size, specific surface area, phases involved, surface chemistry, band gap, and photoluminescence using various analytical techniques, such as scanning electron microscopy, transmission electron microscopy, Brunauer, Emmett, and Teller surface-area measurement, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet-visible spectrophotometry, and spectrofluorometry, respectively. The photocatalytic activity of pure and silver oxide/silver-deposited nanocrystalline anatase titania has been measured by monitoring the degradation of methylene blue dye in an aqueous solution under ultraviolet-radiation exposure. Within the investigated Ag-concentration range, the maximum photocatalytic activity has been observed for 0.1 and 10 mol % Ag for the chemical-reduction (using stannous ions) and ultraviolet-reduction methods with the corresponding apparent first-order reaction-rate constant (k(app)) values of 0.228 and 0.151 min(-1), which are 3.5 and 2.3 times larger than that of pure nanocrystalline anatase fitania (0.065 min(-1)). The chemical-reduction method (using stannous ions), hence, appears to be more effective than the ultraviolet-reduction method for enhancing the photocatalytic activity of nanocrystalline anatase titania. Various factors such as the surface concentration of superoxide ions, oxygen-ion vacancies, and stannous ions as well as the amount of silver oxide/silver and tin oxide are observed to control the surface-adsorption of methylene blue and photoinduced electron/hole lifetime and, hence, variation in the photocatalytic activity as a function of silver concentration.

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction